2018
DOI: 10.3171/2017.7.jns171166
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation outcomes in patients implanted under general anesthesia with frame-based stereotaxy and intraoperative MRI

Abstract: OBJECTIVE The authors' aim in this study was to evaluate placement accuracy and clinical outcomes in patients who underwent implantation of deep brain stimulation devices with the aid of frame-based stereotaxy and intraoperative MRI after induction of general anesthesia. METHODS Thirty-three patients with movement disorders (27 with Parkinson's disease) underwent implantation of unilateral or bilateral deep brain stimulation systems (64 leads total). All patients underwent the implantation procedure with stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…The main advantage of electrode implantation using iMRI is that electrode trajectory can be accurately implanted and adjusted before final placement by visualizing the intended target [66]. The error after correcting the electrode location using iMRI under GA without MER was similar to the error of using MER [30]. When comparing the electrode location on both sides, the error was smaller in the second insertion side than in the first insertion side, which is presumed to be due to the correction based on the iMRI result after the first insertion.…”
Section: Intraoperative Mrimentioning
confidence: 89%
See 1 more Smart Citation
“…The main advantage of electrode implantation using iMRI is that electrode trajectory can be accurately implanted and adjusted before final placement by visualizing the intended target [66]. The error after correcting the electrode location using iMRI under GA without MER was similar to the error of using MER [30]. When comparing the electrode location on both sides, the error was smaller in the second insertion side than in the first insertion side, which is presumed to be due to the correction based on the iMRI result after the first insertion.…”
Section: Intraoperative Mrimentioning
confidence: 89%
“…Successful clinical results on the intraoperative imaging to verify the accuracy of STN lead position instead of electrophysiological structure mapping or stimulation tests during DBS surgery have been reported [23,29,31,37,[40][41][42][43][44]. In recent studies on the advancement of intraoperative imaging, no significant clinical results were found when compared to awake DBS [16,30,37,45,46]. However, most of these studies are retrospective analyses with a small number of patients and significant heterogeneity in anesthesia and surgical techniques.…”
Section: Using Intraoperative Imagingmentioning
confidence: 99%
“…It has been demonstrated that the clinical outcomes and complication rates of asleep surgery are comparable to those in historical studies using MER to guide or confirm lead placement under LA 12 15 . An advantage of iCT or iMRI guidance is the ability to account for brain shift following dural opening and cerebrospinal fluid loss 16 . The ideal intraoperative imaging modality for use during asleep DBS surgery remains to be confirmed, and further data are needed to provide accurate comparisons between the outcomes of iCT and iMRI.…”
Section: Discussionmentioning
confidence: 99%
“…MCP‐based coordinates are based on the robust landmarks AC and PC and they are the classical language of stereotaxy, but these landmarks are distant to the STN which might lead to errors due to anatomical variation. The ever‐improving quality of MRI scans is increasing the capability to directly visualize the STN as shown by DBS operation under general anesthesia based in intraoperative MRI (Matias, Frizon, Nagel, Lobel, & Machado, ). However, NR is better visualized in MRI than STN and has been found in some studies to more reliable than MCP‐based targeting (Andrade‐Souza et al., ; Houshmand et al., ; Matias et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The ever‐improving quality of MRI scans is increasing the capability to directly visualize the STN as shown by DBS operation under general anesthesia based in intraoperative MRI (Matias, Frizon, Nagel, Lobel, & Machado, ). However, NR is better visualized in MRI than STN and has been found in some studies to more reliable than MCP‐based targeting (Andrade‐Souza et al., ; Houshmand et al., ; Matias et al., ). We suggest that because of anatomical variability and different reliability of the different methods of electrode coordinate acquisition, it may be beneficial to acquire coordinates with at least two different methods.…”
Section: Discussionmentioning
confidence: 99%